1965
DOI: 10.6028/jres.069d.060
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic waves along an infinitely long and thin conducting wire in a magneto-ionic medium

Abstract: Electromagnetic fields of an infinitely long co nducting cylinder in a magneto·ionic medium with axial stati c magnetic fi eld are theoreti call y analyzed. Expressions of the electromagnetic field s and the di spersion formulas are ob taine d. Explicit approximate expressions of the relative propagation constants for th e case of an ex tremely thin wire are derived and their dependence on th e plasma and the cyclotron frequen cies is di scussed. The behavior of th e electromagnetic fi elds around the wire is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1965
1965
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Many papers on this subject have been published in recent years and may roughly be classified into the following four categories: 1) the study of the far-field pattern and radiation resistance of a short dipole with assumed current distribution (Bunkin [l 1, Kogelnik Kuehl [3], Arbel and Felsen [4], Mittra and Deschamps [5], Staras [6], Wait [7], Seshadri [8], and others); 2) the study of the input impedances of a short dipole or a small loop with assumed current distribution by using the quasistatic theory (Balmain [ 9 ] , Duff and Mittra [lo]); 3) the study of the input impedance of a short dipole antenna with assumed sinusoidal current distribution (Ament, Katzin, Katzin, and Koo [ll]); 4) the study of the propagating waves guided along a perfectly conducting infinite wire (Mushiake [12] and Seshadri [13]). …”
Section: Introductionmentioning
confidence: 99%
“…Many papers on this subject have been published in recent years and may roughly be classified into the following four categories: 1) the study of the far-field pattern and radiation resistance of a short dipole with assumed current distribution (Bunkin [l 1, Kogelnik Kuehl [3], Arbel and Felsen [4], Mittra and Deschamps [5], Staras [6], Wait [7], Seshadri [8], and others); 2) the study of the input impedances of a short dipole or a small loop with assumed current distribution by using the quasistatic theory (Balmain [ 9 ] , Duff and Mittra [lo]); 3) the study of the input impedance of a short dipole antenna with assumed sinusoidal current distribution (Ament, Katzin, Katzin, and Koo [ll]); 4) the study of the propagating waves guided along a perfectly conducting infinite wire (Mushiake [12] and Seshadri [13]). …”
Section: Introductionmentioning
confidence: 99%
“…Evaluating H φ (ρ, p) and H z (ρ, p) at ρ = a 0 and substituting them into (18), after some lengthy algebra we arrive at…”
Section: Integral Representation Of the Antenna Currentmentioning
confidence: 99%
“…Then the truncation of the antenna to a finite length is performed, which leads to reflections of current waves of similar type from the antenna ends. Using such a waveguide approach, it was shown that, in general, the current on an uninsulated antenna immersed in a resonant magnetoplasma and excited by a voltage source comprises contributions from an eigen (bound) mode, which can exist in some frequency bands [18,19], and from continuous-spectrum waves [14,17]. In some cases important for applications, the eigenmode contribution is found to dominate the current distribution on a fairly thin antenna excited by a delta-function voltage source [17].…”
Section: Introductionmentioning
confidence: 99%
“…Because the high-frequency extremities of the observed curves can be fitted well to (2) by adjusting it is worthwhile to see what happens when the surrounding dielectric is changed to that of a cold magnetoplasma. Mushiake [1965] .............. •,,, ' .............. . ............... • .…”
Section: Without a Sheathmentioning
confidence: 99%